The Effect of AI Identity Threat on Psychological Distress, Mediated by Cognitive Job Insecurity, Among Freelance Graphic Designers in Bandung (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2026)
The rapid development of generative artificial intelligence (AI) has posed an identity threat to creative workers, including freelance graphic designers who lack the structural protections inherent in formal employment. This study aims to analyze the effect of AI Identity Threat on Psychological Distress, with Cognitive Job Insecurity as a mediating variable, among freelance graphic designers in Bandung. Utilizing an explanatory quantitative approach with a cross-sectional design, data were collected via an online questionnaire from 145 respondents selected through a purposive sampling technique. The data were subsequently analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) via SmartPLS 4. The results indicate that AI Identity Threat has a positive and significant effect on Cognitive Job Insecurity ($β$ = 0.636; $p$ < 0.05). Furthermore, Cognitive Job Insecurity has a positive and significant effect on Psychological Distress ($β$ = 0.496; $p$ < 0.05), and AI Identity Threat exerts a direct positive and significant effect on Psychological Distress ($β$ = 0.204; $p$ < 0.05). The mediation analysis reveals that Cognitive Job Insecurity partially mediates the effect of AI Identity Threat on Psychological Distress ($β$ = 0.316; $p$ < 0.05). These findings confirm that the psychological impact of AI-driven identity threats on creative freelancers is predominantly channeled through cognitive evaluations of job sustainability, aligning with the perspective of Social Identity Theory.